2007
DOI: 10.1016/j.jpowsour.2007.04.059
|View full text |Cite
|
Sign up to set email alerts
|

Pore network modeling of fibrous gas diffusion layers for polymer electrolyte membrane fuel cells

Abstract: A pore network model of the gas diffusion layer (GDL) in a polymer electrolyte membrane fuel cell is developed and validated. The model idealizes the GDL as a regular cubic network of pore bodies and pore throats following respective size distributions. Geometric parameters of the pore network model are calibrated with respect to porosimetry and gas permeability measurements for two common GDL materials and the model is subsequently used to compute the pore-scale distribution of water and gas under drainage co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
276
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(284 citation statements)
references
References 34 publications
8
276
0
Order By: Relevance
“…For this reason, it is recommended that a 5 th -order dependence is set to be the maximum that can be obtained; the order dependence of around 2 to 5 agrees with recent pore-network modeling studies [19][20][21]. It should be noted that for this paper, the differential impacts of changing properties is being explored and not the exact magnitude.…”
Section: Updated Porous-medium Model and Modeling Methodologymentioning
confidence: 81%
See 2 more Smart Citations
“…For this reason, it is recommended that a 5 th -order dependence is set to be the maximum that can be obtained; the order dependence of around 2 to 5 agrees with recent pore-network modeling studies [19][20][21]. It should be noted that for this paper, the differential impacts of changing properties is being explored and not the exact magnitude.…”
Section: Updated Porous-medium Model and Modeling Methodologymentioning
confidence: 81%
“…Often, a Bruggeman-type relation is used where n = 1.5; however, recent microscopic simulations and experimental studies have suggested that the value is closer to between 2 and 5 for typical GDLs [5,14,19,20,24,39,40,64]. Although, it should be noted that some of these studies change the volume fraction by compression, which alters the pore network and is different than examining a change in tortuosity and volume fraction due to pore filling.…”
Section: Updated Porous-medium Model and Modeling Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The pressure-volume function may be constant (7,11,12), may vary as a function of the meniscus position inside the pore mimicking pore throat effect (16), or by defining an irregular pore shape (15).…”
Section: Pore-network Model and Simulationmentioning
confidence: 99%
“…Subsequently, Pasaogullari and Wang (Pasaogullari & Wang, 2004a) developed a theory describing liquid water transport in hydrophobic GDL, and explored the effect of GDL wettability on liquid water transport. Recently, Sinha and Wang (Sinha & Wang, 2007, Gostick et al (Gostick et al, 2007) and Rebai and Prat (Rebai & Prat, 2009) have developed a pore-network model to understand the liquid water transport in a hydrophobic GDL with the GDL morphology taken into account.…”
Section: Introductionmentioning
confidence: 99%